Decreased expression of 14-3-3 in Paracoccidioides brasiliensis confirms its involvement in fungal pathogenesis (2016)
ABSTRACT : The interaction between the fungal pathogen Paracoccidioides brasiliensis and host cells is usually mediated by specific binding events between adhesins on the fungal surface and receptors on the host extracellular matrix or cell surface. One molecule implicated in the P. brasiliensis-host interaction is the 14-3-3 protein. The 14-3-3 protein belongs to a family of conserved regulatory molecules that are expressed in all eukaryotic cells and are involved in diverse cellular functions. Here, we investigated the relevance of the 14-3-3 protein to the virulence of P. brasiliensis. Using antisense RNA technology and Agrobacterium tumefaciens-mediated transformation, we generated a 14-3-3-silenced strain (expression reduced by~55%). This strain allowed us to investigate the interaction between 14-3-3 and the host and to correlate the functions of P. brasiliensis 14-3-3 with cellular features, such as morphological characteristics and virulence, that are important for pathogenesis.